Epidemic, risk factors of carbapenem-resistant Klebsiella pneumoniae infection and its effect on the early prognosis of liver transplantation - Liu, Ning; Yang, Gengxia; Dang, Yan; Liu, Xin; Chen, Ming; Dai, Fangfang; Ding, Xiurong; Li, Wenlei; Li, Guangming; Lou, Jinli; Chen, Dexi; Yu, Yanhua (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection remains a major cause of morbidity and mortality in early-stage post-liver transplantation (LT). Methods: We retrospectively analyzed the demographic, clinical, infection characteristics, and the 3-months post-LT prognosis of all patients who received LT in our hospital between January 2019 and December 2021. Results: Among the 272 LT recipients, sixty-two cases (22.8%) had at least one infection within 3-months post-LT. Twenty-eight recipients were dead with bacteria infection. Twelve recipients were dead with CRKP infection. The risk factors independently related to 3-months mortality were age (Odds ratio (OR)= 1.126, 95% Confidence interval (CI): 1.009 1.257; P=0.034), mechanical ventilation (MV) (OR=1.206, 95% CI: 1.039 1.401; P =0.014), and CRKP infection (OR=18.240, 95% CI: 2.206 150.842; P =0.007). In CRKP infection, the length of ICU stay (OR=1.067, 95% CI: 1.015 1.122; P=0.011), pre-operation infection (POI) (OR=6.733, 95% CI: 1.160 39.088; P=0.034), and hepatocellular carcinoma (HCC) (OR=26.772, 95% CI: 1.747 410.187; P=0.018) were the independent risk factors. With COX multivariate regression analysis, the 3-months survival rate of CRKP infected recipients was significantly lower than that without CRKP infection post-LT. Conclusions: CRKP infection is closely correlated with poor prognosis in 3-months post-LT.